Urinary Metabolomic Profile in Children with Autism Spectrum Disorder - Osredkar, Joško; Kumer, Kristina; Godnov, Uroš; Jekovec Vrhovšek, Maja; Vidova, Veronika; Price, Elliott James; Javornik, Tara; Avguštin, Gorazd; Fabjan, Teja (International journal of molecular sciences, 2025)
Autism spectrum disorder (ASD) has been associated with disruptions in tryptophan (TRP) metabolism, affecting the production of key neuroactive metabolites. Investigating these metabolic pathways could yield valuable biomarkers for ASD severity and progression. We included 44 children with ASD and 44 healthy children, members of the same family. The average age in the ASD group was 10.7 years, while the average age in the control group was 9.4 years. Urinary tryptophan metabolites were quantified via liquid chromatography-mass spectrometry operating multiple reaction monitoring (MRM). Urinary creatinine was analyzed on an Advia 2400 analyzer using the Jaffe reaction. Statistical comparisons were made between ASD subgroups based on CARS scores. Our findings indicate that children with ASD have higher TRP concentrations (19.94 vs. 16.91; p = 0.04) than their siblings. Kynurenine (KYN) was found at higher levels in children with ASD compared to children in the control group (82.34 vs. 71.20; p = 0.86), although this difference was not statistically significant. The ASD group showed trends of higher KYN/TRP ratios and altered TRP/ indole-3-acetic acid (IAA) and TRP/5-hydroxyindoleacetic acid (5-HIAA) ratios, correlating with symptom severity. Although the numbers of the two groups were different, our findings suggest that mild and severe illnesses involve separate mechanisms. However, further comprehensive studies are needed to validate these ratios as diagnostic tools for ASD.
Keywords: kyselina hydroxyindoloctová; Tryptophan; poruchy autistického spektra; tryptofan; metabolomika; Metabolomics; Kynurenine; mladiství; Autism Spectrum Disorder; tryptophan; CARS; mužské pohlaví; metabolom; autism spectrum disorder; studie případů a kontrol; dítě; Child; Metabolome; ženské pohlaví; Humans; Hydroxyindoleacetic Acid; biologické markery; kynurenin; Case-Control Studies; Biomarkers; kynurenine; Female; Adolescent; lidé; Male